Survey of the reading habits among ITM students in Perlis / Cheang Eng Kwong and Iskandar Zulkarnain - Cheang, Eng Kwong; Zulkarnain, Iskandar (Biro Penyelidikan dan Perundingan, Institut Teknologi MARA, 1994)
The subject of the study was sampled from the students of the ITM Perlis branch with the objective of relating their reading habits to family background, gender and by courses and level of their study. The findings show a relationship between these variables and the students' reading habits.